Investigation of Varactor Diode for Frequency Selectivity in Wireless Communication - Rohim, Siti Nabilah; Sanudin, Rahmat (Evolution in Electrical and Electronic Engineering, 2022)
Since the COVID-19 pandemic, began in the past two years, demand for mobile services has increased significantly across the world. Reconfigurable antennas are an indispensable component in wireless communication applications as they used varactor diodes as switching components to tune resonant frequency. In this paper, the varactor diode will be investigated as a part of tuning frequency agility in reconfigurable for Wireless Local Area Networks (WLAN). The electrical characteristics of the varactor diode that will be presented using MATLAB are capacitance-voltage (C-V) and frequency-voltage (F-V). Furthermore, two reconfigurable antennas which are microstrip patch and microstrip inset-fed are being investigated based on the reflection coefficient and elevation radiation pattern. Generally, the resonant frequency can be analysed based on the selective capacitance values where a small value of capacitance gives a wide range of resonant frequencies by varying the reverse bias varactor voltage. Simulation results show that both antennas are successfully addressed for investigating the antenna radiation pattern at the targeted frequency of 5GHz using the varactor diode as a feed element. Therefore, it is concluded that the varactor diode managed to aid in frequency tuning into the targeted frequency in the reconfigurable antennas.